Waste to energy: A STEM-ESD approach to improve student awareness and action in converting waste into eco-friendly energy - Rini Solihat; Baharudin Yusuf Haqiqi; Ari Widodo (University of Muhammadiyah Malang, 2024)
Waste management is a significant issue in Indonesia, and awareness and actions across all sectors, including school students, play a critical role. This study investigates the impact of educational interventions on students' awareness and actions regarding waste management and its potential as a source of environmentally friendly energy. The research used a quasi-experimental design, specifically a non-equivalent control group, involving a sample of 44 tenth-grade students in Bandung who were studying environmental change. Participants were selected through purposive sampling, and data were gathered via a questionnaire. Results indicate that the intervention significantly improved students' awareness of utilizing waste as an eco-friendly energy source (p = 0.009 < α = 0.05), although it did not significantly influence their actions to apply this knowledge (p = 0.201 > α = 0.05). This study provides an initial perspective on the potential of STEM-ESD project-based learning to enhance students' awareness and practical engagement in sustainable waste management practices.